Leadership and Organizational Vision ÃÂÃÂ¢ÃÂÃÂÃÂÃÂ Hopes, Concepts and Reality. - Clarke, Dave (2006)
This is an exploratory study of the challenges a particular business leader faces in bringing his organizational vision to life. It seeks to understand some of the fundamental issues relating to how the vision needs to be conceived, structured and communicated but more importantly tries to uncover some of the specific roadblocks that might be faced along the way. This involved a critique of the culture within Diageo with specific emphasis on the gaps between actual and desired and ÃÂÃÂ¢ÃÂÃÂÃÂÃÂofficialÃÂÃÂ¢ÃÂÃÂÃÂÃÂ and ÃÂÃÂ¢ÃÂÃÂÃÂÃÂunofficialÃÂÃÂ¢ÃÂÃÂÃÂÃÂ cultures Data gathered using focus groups, semi-structured interviews and direct observation is analyzed using a theoretical framework that critically examines the link between organizational success, vision and culture. What this study finds is that success is derived from a mixture of consistency and alignment and that a strong culture is a fundamental building block of delivering an organizational vision. Truly understanding the gaps and reasons behind the gaps is the first stage in creating a congruent and powerful culture. There are no short cuts to success and Jim Young must reevaluate his goals, timelines and action plan if he is to create his desired future for the Diageo On Trade team